What is the added value of FeNO as T2 biomarker? - Marcos, María Celeste; Cisneros Serrano, Carolina (Frontiers in Allergy, 2022)
There is increasing evidence about the role of nitric oxide in type 2 (T2) immune response. Fraction of exhaled nitric oxide (FeNO) is a product of airways inflammation and it is increased in patients with asthma. Since Gustaffson published the first article about this biomarker in the 1990s, interest has continued to grow. Compared with other T2 biomarkers such as blood eosinophil count, induced sputum, or serum periostin, FeNO has some remarkable advantages, including its not invasive nature, easy repeatability, and possibility to be performed even in patients with severe airway obstruction. It is considered as an indicator of T2 inflammation and, by the same token, a useful predictor for inhaled steroid response. It is difficult to determine the utility of nitric oxide (NO) for initial asthma diagnosis. In such a heterogenous disease, a single parameter would probably not be enough to provide a complete picture. There is also an important variability among authors concerning FeNO cutoff values and the percentage of sensibility and specificity for diagnosis. Its high specificity indicates a potential role to “rule in” asthma; however, its lower sensibility could suggest a lower capacity to “rule out” this pathology. For this reason, if a diagnosis of asthma is being considered, FeNO should be considered along with other tests. FeNO has also shown its utility to detect response to steroids, adherence to treatment, and risk of exacerbation. Even though there is not enough quality of evidence to establish overall conclusions, FeNO could be an alternative procedure to diagnose or exclude asthma and also a predictive tool in asthma treated with corticosteroids.